The allometry of vertebrate pursuit predation - Lars Koopmans; André M. de Roos; Benjamin T. Martin (Proceedings of the National Academy of Sciences, 2026)
Pursuit and evasion dynamics are a general phenomenon observed in predator–prey interactions across terrestrial, aquatic, and aerial domains. Differences in body mass and domain generate variation in biomechanical traits that shape these encounters, yet the consequences of such variation remain poorly understood. Here, we integrate allometric scaling relationships of vertebrate locomotion with turning gambit theory, a geometrical model of pursuit–evasion, to examine how body size and domain shape predator–prey encounter outcomes. We show that in its original form, the turning gambit predicts that prey should rarely be able to outmaneuver predators, particularly in aerial and aquatic systems, contradicting the low capture success observed in nature. This mismatch is resolved by recognizing that predators cannot respond instantaneously to prey maneuvers. Such sensory–motor delays, although brief, shift the advantage to prey across all domains. Finally, we show that these delays, together with domain-specific scaling of speed and maneuverability, generate distinct biomechanical regimes in which different traits govern pursuit–evasion outcomes.